2020
DOI: 10.1016/j.neuroimage.2020.116995
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel whole-head OPM-MEG: Helmet design and a comparison with a conventional system

Abstract: Magnetoencephalography (MEG) is a powerful technique for functional neuroimaging, offering a non-invasive window on brain electrophysiology. MEG systems have traditionally been based on cryogenic sensors which detect the small extracranial magnetic fields generated by synchronised current in neuronal assemblies, however, such systems have fundamental limitations. In recent years, non-cryogenic quantum-enabled sensors, called optically-pumped magnetometers (OPMs), in combination with novel techniques for accura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 212 publications
(230 citation statements)
references
References 65 publications
5
218
0
1
Order By: Relevance
“…Considering the effect of the data-driven beamforming approaches, the beamforming BCG corrected data revealed significantly greater motor beta ERD as compared to the beamforming+AAS BCG corrected data, whereas there was no significant difference in the visual alpha ERD. Additionally, the locations of visual alpha VEs in the visual cortex were consistent with the previous findings when the visual stimuli were used to trigger movement executions (Brookes et al, 2005;Scheeringa et al, 2011;Wilson et al, 2019), whereas the locations of motor beta VEs were found as expected in the right motor cortex contralateral to the left-hand button presses (Hill et al, 2020;Wilson et al, 2019). Based on these robust visual alpha ERD and motor beta ERD and VE locations, our findings revealed that our data-driven beamforming approaches did not only suppress the BCG artefacts, but also recovered meaningful task-based neural signals induced by the ANT task (Fan et al, 2007;Marshall et al, 2015).…”
Section: Task-based Induced Neural Activity In Eeg-fmrisupporting
confidence: 89%
See 1 more Smart Citation
“…Considering the effect of the data-driven beamforming approaches, the beamforming BCG corrected data revealed significantly greater motor beta ERD as compared to the beamforming+AAS BCG corrected data, whereas there was no significant difference in the visual alpha ERD. Additionally, the locations of visual alpha VEs in the visual cortex were consistent with the previous findings when the visual stimuli were used to trigger movement executions (Brookes et al, 2005;Scheeringa et al, 2011;Wilson et al, 2019), whereas the locations of motor beta VEs were found as expected in the right motor cortex contralateral to the left-hand button presses (Hill et al, 2020;Wilson et al, 2019). Based on these robust visual alpha ERD and motor beta ERD and VE locations, our findings revealed that our data-driven beamforming approaches did not only suppress the BCG artefacts, but also recovered meaningful task-based neural signals induced by the ANT task (Fan et al, 2007;Marshall et al, 2015).…”
Section: Task-based Induced Neural Activity In Eeg-fmrisupporting
confidence: 89%
“…Since the alpha and beta ERD exhibits power reduction when compared to the baseline, signal to noise ratios (SNRs) at the sensor and source levels were calculated as the absolute value of the difference. Then group mean SNR value was calculated by averaging SNR value across all trials first and then across subjects as suggested in Hill et al (2020), for each electrode (non-BCG corrected; AAS BCG corrected) and each VE location (beamforming+AAS BCG corrected; beamforming BCG corrected). The active and control baseline time windows were consistent throughout the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…"wearable" systems in which (if background fields are controlled appropriately) subjects can move their head freely during data acquisition (Boto et al, 2018). OPM arrays are beginning to be developed with up to 50 sensors surrounding the head (Hill et al, 2020) and there is a growing argument that these deviceswhich are also cheaper than conventional MEGwill ultimately supersede the current generation of MEG scanners. However, OPM-MEG remains a nascent technology and if the functional neuroimaging field is to gain confidence in it, OPMbased systems must be able to do everything a SQUID system can do.…”
mentioning
confidence: 99%
“…OPMs is less affected by the head movement compared to conventional MEG, and can be worn more conveniently because of the sensors' positions on the scalp (Boto et al 2019). Although OPMs is not yet used clinically, there have been some recent studies using OPMs in several areas (Barry et al 2019;Borna et al 2020;Boto et al 2019;Elzenheimer et al 2020;Hill et al 2020;Iivanainen et al 2020;Lin et al 2019;Nardelli et al 2019). OPMs has not yet been used in HFO research, but this is a very promising future application of this technology.…”
Section: Challenges In Noninvasive Hfo Researchmentioning
confidence: 99%